The Higher Level Assignment of Financial Mathematics: How to Design it? - Ramadhan, M. Hasbi; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Resti, Yulia (Universitas Wiralodra, 2025)
This research aimed to design financial mathematics assignment based on Pendidikan Matematika Realistik Indonesia (PMRI) approach and de Lange's theory to get validity, practicality, and effects of potential. In designing, we also consider the fundamental characteristics of financial mathematics including relevance, representational faithfulness, verifiability, timeliness, understandability, and comparability. We used development studies on design research method. This research was conducted at Vocational High School (VHS) 1 Jambi City in XI grade of Accounting Major. We collected the data through documentation, observation, interview, and tests. As a result, this research products the higher level assignment of financial mathematics based on PMRI approach and de Lange theory that is valid, practical, and have potential effects with consider the fundamental characteristics of financial mathematics. The results of research also found that, students became more understanding in financial activities. Moreover, it also can be used as a consideration to VHS for designing financial mathematics assignments.